Corporate social responsibility and firm performance in the financial industry in Vietnam: The mediating role of digital transformation - Danh, Luu Xuan; Long, Nguyen Thanh; Khoa, Tran Dang (Nurture, 2024)
Purpose: This study evaluated the influence of corporate social responsibility (CSR) initiatives undertaken by banks in Vietnam on their overall performance. Additionally, it sought to examine the relationship between corporate social responsibility and digital transformation efforts within the framework of the ongoing Fourth Industrial Revolution. Design/Methodology/Approach: The research uses a survey sample from Southeast Vietnam, specifically Binh Duong Province, Dong Nai Province, Tay Ninh Province, Ba RIA Vung Tau Province and Ho Chi Minh City. A total of 245 valid questionnaires were gathered from mid- and senior-level executives, senior employees and department heads who have implemented digital transformation strategies in banks. Findings: This study explores the relationship between corporate social responsibility and firm performance in Vietnam’s financial industry focusing on the banking sector. The study discovered a favourable relationship between corporate social responsibility (CSR) and enterprise digital transformation as well as a good relationship between CSR and digital transformation and Vietnamese banks’ business success. Conclusion: The digital economy has increasingly contributed to global economic development. Today’s digital landscape is undergoing a widespread phenomenon known as digital transformation. Hence, it is crucial to examine the impact of digital transformation on business processes. Practical Implications: The data also supports the idea that digital transformation serves as a mediator between corporate CSR and financial performance contributing to filling the gap when there is limited research in Vietnam on this relationship. Contribution to the Literature: This research aims to help banks in Vietnam enhance operational efficiency when banks actively engage in CSR and digital transformation.